Development of Classical Fiqh towards Contemporary: Relevance of Thought of Islamic Figures and Operational Transformation of Fiqh Products - Umi Latifah; Ida Nurlaeli; Ulfi Zulfikar Faridhun (The Institute of Research and Service Community IPMAFA Pati, 2023)
The purpose of writing the article is expected to reflect on the thoughts of Islamic figures who have contributed to the welfare of the fiqh muamalah field, as well as to review the operational transformation of fiqh products from time to time. The need for actualization to guide in responding to the challenges or problems of today's society makes it important to reflect on the historical development of the relation to fiqh muamalah that existed before. The method used in this paper is to collect various sources of literature from previous research or library research for descriptive analysis and find the values. As for the results, the authors found that the thoughts of Islamic figures such as Abu Yusuf, Al-Ghazali, Ibn Khaldun, and Ibn Taimiyah still have relevance in the present, the operational fiqh in the development of the classical period can still be drawn from its elasticity. This provides enthusiasm for young scholars to continue to develop their thoughts in providing benefits to their environment by upholding sharia principles, tabarru agreements between people, and the spirit of exploring Islamic treasures in responding to today's problems.